2003
DOI: 10.1038/nbt806
|View full text |Cite
|
Sign up to set email alerts
|

Immunotargeting of catalase to the pulmonary endothelium alleviates oxidative stress and reduces acute lung transplantation injury

Abstract: Vascular immunotargeting may facilitate the rapid and specific delivery of therapeutic agents to endothelial cells. We investigated whether targeting of an antioxidant enzyme, catalase, to the pulmonary endothelium alleviates oxidative stress in an in vivo model of lung transplantation. Intravenously injected enzymes, conjugated with an antibody to platelet-endothelial cell adhesion molecule-1, accumulate in the pulmonary vasculature and retain their activity during prolonged cold storage and transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 39 publications
10
155
0
Order By: Relevance
“…Most likely, lag between peak anti-TM/GOX targeting and manifestation of its effect reveals the time interval that is necessary to generate sufficiently toxic amount of H 2 O 2 in the pulmonary vasculature and cause the oxidative stress that takes a few hours to develop into vascular edema. Consistent with the fact that endothelium degrades delivered conjugates within a few hours [46,49,53], a more prolonged hyperoxia did not aggravate further the injury: enhanced supply of the substrate makes no difference when the targeted enzyme is gone.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Most likely, lag between peak anti-TM/GOX targeting and manifestation of its effect reveals the time interval that is necessary to generate sufficiently toxic amount of H 2 O 2 in the pulmonary vasculature and cause the oxidative stress that takes a few hours to develop into vascular edema. Consistent with the fact that endothelium degrades delivered conjugates within a few hours [46,49,53], a more prolonged hyperoxia did not aggravate further the injury: enhanced supply of the substrate makes no difference when the targeted enzyme is gone.…”
Section: Discussionsupporting
confidence: 62%
“…We tested distribution of the radiolabeled TM antibodies and GOX conjugates one hour after IV injection. Previous studies of immunotargeting of radiolabeled conjugates directed to highly accessible endothelial determinants such as TM, angiotensin-converting enzyme (ACE), PECAM-1, intercellular adhesion molecule 1 (ICAM-1) and GP90 showed that their maximum uptake in the lungs occurs within 15-30 min, followed by a short 15-30 min stable period and subsequent reduction of the pulmonary level observed at times more than one hour after IV injection [22,25,27,[46][47][48][49][50][51][52]. Therefore, the kinetics of lung edema development showing a maximum 4 hour after injection of a lower dose of the conjugate selected to avoid overt early lethality (Fig.4C) is not due to delayed accumulation of GOX in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, intemalization of anti-ICAM-1 or anti-PECAM-1 conjugates was dependent on antigen clustering, and a critical parameter for intemalization was conjugate size (100 [211] and induces acute oxidative endothelial injury in murine lungs after IV injection [212]. Recent studies indicate that anti-CAM/catalase conjugates bind to and enter EC, which protects endothelium against oxidant stress in cell cultures [75,213] and in animals [214].…”
Section: Mechanisms Of Endothelial Endo-cytosismentioning
confidence: 99%
“…This intemalization pathway delivers materials to lysosomal compartments with unusually slow kinetics (around 3 h) [253]. Conjugation of catalase to anti-ICAM-1 or anti-PECAM-1 antibodies permits intracellular delivery of the active enzyme to EC, and provides anti-oxidant protection for a relatively prolonged window time due to the slow kinetics of delivery to lysosomes [214,253].…”
Section: Intracellular Trafficking and Fate Of Internalized Materialsmentioning
confidence: 99%
“…These studies have important implications as endothelial dysfunction plays an important role in a number of pulmonary diseases such as pulmonary hypertension, adult respiratory distress syndrome, or metastatic disease to the lung. For example, targeted delivery of catalase to pulmonary ECs has been shown to offer lung protection in several models of lung injury (7)(8). Nucleic acidbased drugs are currently being explored as novel therapeutics, and they also hold promise for the treatment of pulmonary vascular diseases (9).…”
Section: Introductionmentioning
confidence: 99%